Development of a wireless home security system - Ng, George Wai Onn. (2009)
In this project report, a wireless home security system utilising spread spectrum technology is proposed. The requirements of such a system are investigated, and system specifications are developed. The crux of a spread spectrum system is the synchronisation module, and within that module, the first step toward achieving synchronisation depends on the acquisition module.